Free Trade and Exploitation - Dimitriu, Cristian (Daimon Revista Internacional de Filosofia, 2014)
Abstract. According to a popular view, defended by Pogge and other, trade agreements between wealthy and poor countries, as currently structured, are coercive and unfair for developing countries. Against this view, I argue that such agreements should be understood as exploitative instead of coercive. The difference between these two notions is a substantial one, as in the case of coercive proposals one of the parties is made worse off, while in the case of exploitative proposals both parties improve their situation. I rely on familiar accounts of coercion and exploitation, defended by Wertheimer, to make this point.